Reported MPC in the Presence of Debt - Hector Sala; Pedro Trivín (Institute of Labor Economics (IZA), 2021)
We use information from the last wave of the Spanish Survey of Households Finance to study the influence of debt on the self-reported Marginal Propensity to Consume (MPC). The MPC is 43 per cent on average, but indebted households have a smaller MPC than non-indebted households. This negative association increases along with the amount of debt. We also find a lower MPC for households that were subject to liquidity constraints in the previous year, and for those whose reference person is self-employed. We observe that the past relationship between income and consumption is also an important determinant of the MPC as households that invest last year's savings, or hold them for the future, have again a lower MPC. These factors are in line with the predictions of precautionary saving models.
Keywords: D12; D14; E21; 330; marginal propensity to consume; debt; survey